The Incidence of Measles Infection in Southern Vietnam during COVID-19 Pandemic - M. Hoang; A. Yu. Antipova; I. N. Lavrentieva; V. V. Zarubaev (Эпидемиология и вакцинопрофилактика)
The paper presents data on measles cases identified in 18 provinces of South Vietnam (SV) in 2020, during the active phase of the pandemic of the new coronavirus SARS-CoV2. The measles virus actively circulated in SV in the first months of 2020: the average measles incidence rate was 1.27 per 100,000 population. Children under 5 years of age dominated in the age structure (71%). The vast majority of cases are people who have not been vaccinated against measles, as well as people who do not have information about vaccinations; in total, their share was 97.4%, but there were vaccinated and revaccinated individuals among the sick. Significantly more often, IgM-measles antibodies were recorded in samples obtained from the city of Can Tho, (n=57) where the infectious diseases hospital is located, receiving patients from neighboring regions of the SV. The largest number of measles cases were also recorded in the provinces of Dong Thap (n=57), Hao Glang (n=62) and Ho Chi Minh City (n=15). That is, residents of large cities, industrial and the medical centers were primarily involved in the measles epidemic process. A sharp decrease in the incidence of measles has been shown since April 2020, when measures to limit the spread of COVID-19 were introduced in SV. It should be noted that violations of vaccination associated with the COVID-19 pandemic, after the lifting of sanitary and epidemiological restrictions, may lead to increased morbidity and the development of measles outbreaks in Vietnam and other countries involved in the pandemic. Therefore, preventing future outbreaks will require strengthening measles surveillance and control measures to achieve its elimination.